Чёрный котёл: сказочная хроника / Ллойд Александер - Александер Ллойд (Замок чудес, 1995)
Экземпляры: ф. 3 (20090918) / Инвентарный номер: 94859 / Цена: 35.00 / Авт.знак: А 46 / ГРНТИ: 17.82 / ББК: 84(7Сое)